2016
DOI: 10.1021/acs.jpclett.6b01099
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Doping in Quantum-Dots-Based Dilute Magnetic Semiconductor

Abstract: Effective manipulation of magnetic spin within a semiconductor leading to a search for ferromagnets with semiconducting properties has evolved into an important field of dilute magnetic semiconductors (DMS). Although a lot of research is focused on understanding the still controversial origin of magnetism, efforts are also underway to develop new materials with higher magnetic temperatures for spintronics applications. However, so far, efforts toward quantum-dots(QDs)-based DMS materials are plagued with probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 58 publications
3
45
0
Order By: Relevance
“…But, in co-doped ZnO with Cu and Fe, X-ray absorption spectroscopy (XAS) clearly showed the presence of both Fe +2 and Fe +3 and its relative percentage is dependent on the presence of Cu as a dopant. Another research revealed that the size of Fe doped CdS QD was responsible for the magnetic moment [57]. They have achieved a magnetic moment of 80 memu/g at RT for doped CdS and undoped CdS showed negligible amount of magnetic moment with the same scale reaction.…”
Section: Properties and Applications Of Dmsqdsmentioning
confidence: 97%
See 1 more Smart Citation
“…But, in co-doped ZnO with Cu and Fe, X-ray absorption spectroscopy (XAS) clearly showed the presence of both Fe +2 and Fe +3 and its relative percentage is dependent on the presence of Cu as a dopant. Another research revealed that the size of Fe doped CdS QD was responsible for the magnetic moment [57]. They have achieved a magnetic moment of 80 memu/g at RT for doped CdS and undoped CdS showed negligible amount of magnetic moment with the same scale reaction.…”
Section: Properties and Applications Of Dmsqdsmentioning
confidence: 97%
“…Clustering and surface doping are two main issues that are faced during the synthetic process for obtaining uniformed DMSQDs. To eliminate these key issues, one has to overcome selfpurification [57] of the materials and understand the reactivity between the host-guest materials [58,59]. The self-purification is a process where host molecule expels the guest molecule from the surface to attain a thermodynamically stable state by reducing its defect energy.…”
Section: Synthesis Of Dmsqdsmentioning
confidence: 99%
“…Later Saha et al 47 showed in 2016 that self-purification of dopants, previously considered a bane, could be used as a boon for synthesis of uniformly doped QDs of required size. In this process, a small magnetic core was synthesized (demonstrated with the example of Fe 3 O 4 ) and was overcoated with a thick semiconducting shell (CdS).…”
Section: Synthesis Of Dms Qdsmentioning
confidence: 99%
“…It was demonstrated using X-ray absorption spectroscopy (XAS) that both Fe 2+ and Fe 3+ species were present and the relative percentage of the species was dependent on the presence of Cu as a dopant. More recently, it was observed that upon synthesis of DMS QDs using the insideout method 47 , it was possible to obtain much higher magnetic moment compared to earlier counterparts. In this work, it was shown that smaller QDs showed a moment of 80 memu/g at room temperature and the surface-only magnetism on undoped CdS also shown in the same scale was negligible.…”
Section: Properties Of Dms Qdsmentioning
confidence: 99%
See 1 more Smart Citation